2021
DOI: 10.1051/0004-6361/202039801
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere of Betelgeuse before and during the Great Dimming event revealed by tomography

Abstract: Context. Despite being the best studied red supergiant star in our Galaxy, the physics behind the photometric variability and mass loss of Betelgeuse is poorly understood. Moreover, recently the star has experienced an unusual fading with its visual magnitude reaching a historical minimum. The nature of this event was investigated by several studies where mechanisms, such as episodic mass loss and the presence of dark spots in the photosphere, were invoked. Aims. We aim to relate the atmospheric dynamics of Be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…However, later sub-millimeter observations and TiO photometry 12 have favored a singular or multiple dark and cool photospheric spots to explain the event 13 while preserving compatability with optical spectrophotometry, arguing in favor of a molecular opacity increase. A similar conclusion is reached by tomography from high resolution spectroscopy, which suggests that the propagation of two shock waves in the upper atmosphere, aided by underlying convection or outward gas motion altered the molecular opacity in the line of sight 14 . This scenario would be compatible with both anterior spectropolarimetric imaging 15 , and 3D simulations of stellar convection in evolved stars carried out with the CO5BOLD code [16][17][18][19] .…”
Section: Main Papersupporting
confidence: 64%
“…However, later sub-millimeter observations and TiO photometry 12 have favored a singular or multiple dark and cool photospheric spots to explain the event 13 while preserving compatability with optical spectrophotometry, arguing in favor of a molecular opacity increase. A similar conclusion is reached by tomography from high resolution spectroscopy, which suggests that the propagation of two shock waves in the upper atmosphere, aided by underlying convection or outward gas motion altered the molecular opacity in the line of sight 14 . This scenario would be compatible with both anterior spectropolarimetric imaging 15 , and 3D simulations of stellar convection in evolved stars carried out with the CO5BOLD code [16][17][18][19] .…”
Section: Main Papersupporting
confidence: 64%
“…UV observations of chromospheric variability also indicate the formation of a dense, outflowing structure-possibly enhanced by a timing coincidence with outward motion of the pulsational cycle-just before the event (Dupree et al 2020). The most likely explanation for the dimming, then, was an increase in the opacity of this ouflowing material related to the formation of molecules (see, e.g., evidence from TiO-band monitoring and tomography in Harper et al 2020;Kravchenko et al 2021, anddiscussion in Davies &Plez 2021) and possibly also large-grain dust (e.g., Levesque & Massey 2020). As shown in Figure 4, the evolution of Betelgeuse in V and I from the American Association of Variable Star Observers 8 (AAVSO) as it recovers from near the photometric minimum of the 2019-2020 dimming is remarkably similar to the "red"class variables, though smaller in amplitude.…”
Section: See Region Of "Supergiant Instabilities" In Figures 13 and 1...mentioning
confidence: 99%
“…Three main hypotheses have been suggested as reasons for the dimming, namely changes in pulsation dynamics, star spots and a dust cloud. Combinations of these hypotheses have also been suggested as reasons for the dimming 4,5 . We will explore each of these explanations below, before explaining how the nonlinear dynamics of the light curve can contribute towards understanding the dimming.…”
Section: Overviewmentioning
confidence: 99%
“…In addition, high angular resolution images showed a significant dimming in the southern hemisphere of Betelgeuse during the dimming event 7 . Observations from multiple wavelengths suggest that an outflow from the star itself, enhanced by pulsations, condensed around the southern hemisphere of the star 4,5 . It has also been suggested that the dimming could be explained by an ejection from the star that cools below 3000 K to form molecules, before condensing to dust 8 .…”
Section: Overviewmentioning
confidence: 99%